Preventive use of gabapentin to decrease pain and systemic symptoms in patients with head and neck cancer undergoing chemoradiation. Issue 12 (7th August 2020) - Smith, Derek K.; Cmelak, Anthony; Niermann, Ken; Ghiam, Michael; Lou, Diane; Gilbert, Jill; Gibson, Michael K.; Hawkins, Deborah; Murphy, Barbara A.
Abstract: Background: Radiation for patients with head and neck cancer (HNC) is associated with painful mucositis that impacts the delivery of treatment and contributes to high symptom burden. Methods: This was a prospective, randomized pilot trial. Eligible patients received primary or adjuvant chemoradiation. Patients were randomized to usual care vs usual care plus gabapentin titrated to drug tolerance during radiation. Patients completed a symptom survey at baseline and weekly during therapy. Results: Seventy‐nine patients were enrolled in the study (38 control, 41 treatment). At interim analysis, gabapentin use resulted in a decrease in pain ( P = .004), with the biggest decreases being in the latter weeks of therapy. By week 7, the median pain score in the treatment group was below the 0.25 quantile of the control group. Conclusion: Prophylactic use of gabapentin during chemoradiation for HNC patients resulted in a decrease in pain, neurosensory symptoms, and general systemic symptoms.